Assessment of microbial bioformulation Halo-Zinc on performance of paddy in partially reclaimed sodic soils of Hardoi, Uttar Pradesh - MISHRA, D. K.; ARORA, SANJAY; GAUTAM, C. P.N. (Journal of Soil and Water Conservation, 2021)
An on-farm trial was conducted at KVK Hardoi during Kharif 2017 and 2018 to evaluate the performance of liquid bioformulation (Halo-Zinc) by treating seeds of paddy variety NDR 3112 on yield and it’s parameters in partially reclaimed sodic soils of the district. From average data of trial of two years it was observed that the T2 as seed treatment with Halo-Zinc of paddy variety showed higher average grain yield (46.05 q ha-1) and average straw yield (67.6 q ha-1) as compared to the farmers’ practice (T1 with no seed treatment). Among the yield components assessed, the mean number of effective tillers per plant (239) and the number of grains per panicle (124) in T2 were also higher in comparison to T1 as 226 and 109, respectively. Thus, these traits were considered to be the most important factors responsible for yield gap. Along with this, no zinc deficiency symptoms were observed in treated seed demonstration plots this may be due to enhanced availability of zinc. In economic point of view, the B: C ratio of T2 was (1: 2.75) higher compared to the farmer’s practice (1:2.45).